Methodological aspects of cluster policy formation in Azerbaijan - Aliyeva, Aygun (Technium Social Sciences Journal, 2020)
Foreign experience demonstrates that countries’ strategies in cluster policy differ depending on national traditions and culture of their strategy engineering process, as well as on the cluster concept. Analysis of information sources shows that technical and methodological framework for cluster policy formulation have not been clearly and unambiguously studied in science. The most important methodological document on cluster policy is the European Cluster Memorandum signed by the Member States of the European Union in 2006 [3]. It defined the essence and importance of clusters in innovation development and identified the key provisions of cluster policy. One of the essential methodological issues is the role of government in the formation of clusters. The following factors can be associated with the state’s growing influence on clustering processes: market weakness, increase in the volume and value of public goods; an objective priority of public interest in the context of globalization; the need to protect the national economy in the international economic relations; the need for institutional regulations in the national and global economy. Foreign experience demonstrates that the numerous cluster initiatives running in major developed countries over the last few years have been brought forward by local or regional governments. In relatively small developed countries and in a number of developing countries, the government plays an essential role in the cluster development initiative, especially when local and regional government agencies cannot partner with the private sector. A number of decisions on clusters have been adopted at national level in countries with centralized decision-making process.